2013
DOI: 10.5194/hess-17-1975-2013
|View full text |Cite
|
Sign up to set email alerts
|

Teaching groundwater flow processes: connecting lecture to practical and field classes

Abstract: Abstract. Preparing future hydrogeologists to assess local and regional hydrogeological changes and issues related to water supply is a challenging task that creates a need for effective teaching frameworks. The educational literature suggests that hydrogeology courses should consistently integrate lecture class instructions with practical and field classes. However, most teaching examples still separate these three class components. This paper presents an introductory course to groundwater flow processes taug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…O tej globoko zasidrani (že anti~ni) ideji o vodnih žilah v podzemlju poro~a tudi reinFrieD s sodelavci (2012). V Sloveniji, kjer je skoraj polovica ozemlja na kra�kih tleh (GaMs, 2003), o~itno prevladuje poznavanje kra�kega tipa vodonosnika nad razpoklinskim in medzrnskim. Slednji sicer prevladujejo na Ljubljanskem polju in v ve~ini kotlin, zapolnjenih z aluvialnimi sedimenti, a njihova dinamika podzemne vode je slab�e poznana.…”
Section: Onesnaževanje In Za�~ita Vodnih Virovunclassified
“…O tej globoko zasidrani (že anti~ni) ideji o vodnih žilah v podzemlju poro~a tudi reinFrieD s sodelavci (2012). V Sloveniji, kjer je skoraj polovica ozemlja na kra�kih tleh (GaMs, 2003), o~itno prevladuje poznavanje kra�kega tipa vodonosnika nad razpoklinskim in medzrnskim. Slednji sicer prevladujejo na Ljubljanskem polju in v ve~ini kotlin, zapolnjenih z aluvialnimi sedimenti, a njihova dinamika podzemne vode je slab�e poznana.…”
Section: Onesnaževanje In Za�~ita Vodnih Virovunclassified
“…There are very few studies that investigate student-centred approaches in hydrology teaching, especially in the undergraduate (Thompson et al, 2012). The few that do, do not evaluate their effectiveness (Elshorbagy, 2005) or only by using their own experience and observations (Rustum, 2018), only for one year (Arthurs & Templeton, 2009), or only by using standard official module evaluations and marks (e.g., Hakoun, Mazzilli, Pistre, & Jourde, 2013). In this study, I evaluate the merits of a specific example of student-centred active learning in hydrology over an implementation period of three years, complementing official module evaluation data and student marks with informal student feedback, results from a targeted questionnaire, and interviews with students and lecturers.…”
Section: Introductionmentioning
confidence: 99%
“…A common teaching issue in hydrogeology and for the development of conceptual models relies on the heterogeneity in the prior knowledge of the enrolled students, especially in master degree programs. For simultaneously teaching students from civil and environmental engineering, biology, geology, chemistry, or physics a strategy of teaching involving lecture, field and practical classes appears like the most common option (Blöschl et al, 2012;Hakoun et al, 2013). If the lecturers pay attention to the prior knowledge of the students, which evolves in time (Gleeson et al, 2012), it has been demonstrated that learning is enhanced (Bransford et al, 1999).…”
mentioning
confidence: 99%
“…If the lecturers pay attention to the prior knowledge of the students, which evolves in time (Gleeson et al, 2012), it has been demonstrated that learning is enhanced (Bransford et al, 1999). As a consequence of the broad range of background, it is necessary to provide students with the appropriate basics in groundwater, including flow and transport processes (Gleeson et al, 2012;Hakoun et al, 2013), before subsequent field and practical courses are taught.…”
mentioning
confidence: 99%